(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the specific features of English lessons tailored for pedagogy students. It examines the pedagogical approaches and teaching methodologies that enhance language acquisition, critical thinking, and effective communication skills. The study highlights the importance of integrating practical experiences and collaborative learning in English language instruction. By focusing on the unique needs of future educators, the article aims to provide insights into how English language teaching can be optimized to prepare students for their roles in the educational sector.